2012
DOI: 10.1111/j.1744-7917.2012.01570.x
|View full text |Cite
|
Sign up to set email alerts
|

Male‐killer dynamics in the tropical butterfly,Acraea encedana(Lepidoptera: Nymphalidae)

Abstract: Sex ratio distortion in the tropical butterfly Acraea encedana is caused by infection with a male-killing bacterium of the genus Wolbachia. Previous research on this species has reported extreme female bias, high bacterial prevalences, and full sex role reversal. In this paper, we provide an assessment for the dynamics of the male-killer, based on a survey for sex ratios and Wolbachia prevalences among wild populations of A. encedana in Uganda. The study reveals that Wolbachia infection showed considerable var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…These expectations can serve as a base for testing this hypothesis against field data. In a thorough investigation for population sex ratios, male-killer prevalences and morph ratios in D. chrysippus, A. encedon and A. encedana conducted in Uganda (Hassan et al 2012a(Hassan et al , 2012b, two temporal patterns were found, which are highly consistent with theoretical predictions. Firstly, comparing the bacterial prevalences recorded during (2005)(2006)(2007) with those recorded a few years later (1998)(1999) (Jiggins et al 2000a(Jiggins et al , 2000b(Jiggins et al , 2000c for the three species has shown that the male killer undergoes extensive population dynamics.…”
Section: Testing the Hypothesissupporting
confidence: 70%
“…These expectations can serve as a base for testing this hypothesis against field data. In a thorough investigation for population sex ratios, male-killer prevalences and morph ratios in D. chrysippus, A. encedon and A. encedana conducted in Uganda (Hassan et al 2012a(Hassan et al , 2012b, two temporal patterns were found, which are highly consistent with theoretical predictions. Firstly, comparing the bacterial prevalences recorded during (2005)(2006)(2007) with those recorded a few years later (1998)(1999) (Jiggins et al 2000a(Jiggins et al , 2000b(Jiggins et al , 2000c for the three species has shown that the male killer undergoes extensive population dynamics.…”
Section: Testing the Hypothesissupporting
confidence: 70%
“…[45][46][47] To begin with, Wolbachia prevalences were found to vary between different regions in Africa as well as between different populations of the same region. In a thorough investigation for the dynamics of Wolbachia infection in Uganda, Hassan et al 48,49 found an overall prevalence of 44.7% in A. encedon and 79.1 % in Acraea encedana; considerably lower estimates than these of Jiggins et al 42,43 More importantly, re-investigating the same habitat patches studied by Jiggins et al revealed consistently lower prevalences than that previously reported. This pattern can be explained by considering the male-killer's impact on host metapopulations; populations with extremely high prevalence that were observed by Jiggins were extinct due to the lack of males, and the habitat patches were then recolonized by new immigrants from nearby populations, with initially low bacterial prevalences.…”
Section: Acraea Encedon and A Encedanamentioning
confidence: 74%
“…77 We have suggested a selective scenario, in which colour polymorphism is maintained in the mimicry complex through the repeated extinction episodes experienced by the sympatric populations of the three species as a consequence of male-killers' spread. 80 In aposematic, mimetic species there are two selective forces acting to sustain monomorphism, and both are mediated by predation pressure; first, selection toward within-species convergence, favoring the most abundant form in the species, and second, selection toward between-species convergence, favoring the most abundant form in the mimicry complex. It is easy to see that the output of such selective system is colour monomorphism, as long as within-species and between-species selections are acting harmoniously for long time.…”
Section: The Hidden Link Between Mimetic Polymorphism and Male-killingmentioning
confidence: 99%
See 1 more Smart Citation
“…In some parts of this contact zone, sex ratios are highly female‐biased (Smith et al, 2019 ), raising the possibility that the scarcity of males may result in a failure of females to mate. In other areas, both infection rates and sex ratios vary between the wet and dry seasons (Hassan et al, 2013 ; Herren et al, 2007 ), possibly associated with seasonal migration of the different color morphs (Smith et al, 1997 ).…”
Section: Introductionmentioning
confidence: 99%